Announcing the winners of a first round of funding to take agricultural innovations to scale in Africa - MacMillan, Susan (CGIAR System Organization, 2024)
A ‘Scaling Fund’ was launched late last year by the CGIAR Regional Research Initiative on Diversification in East and Southern Africa, an initiative known also by its Shona-Swahili name, ‘Ukama Ustawi’ (denoting ‘partnership’ and ‘well-being’). This initiative supports climate-resilient agriculture and livelihoods in a dozen countries in East and Southern Africa. It helps millions of smallholders to intensify and diversify their maize-based farming while reducing their risks. It does this by improving extension services and governance frameworks, supporting small and medium enterprises, and adopting a gender and social inclusion lens. This initiative’s Scaling Fund was established specifically to help the region’s farmers to mitigate, and adapt to, climate change.